Commercial gentrification in China and its distribution, development, and correlates: The case of Chengdu - Yang, Qinran; Liu, Yang; Yang, Linchuan (Frontiers in Environmental Science, 2022)
Within the Anglo-American literature, commercial, along with residential, gentrification has often been treated as an attendant neighborhood phenomenon. This study aims to uncover the distribution of areas for emerging consumption that indicate the occurrence of commercial gentrification, as well as to explain the development process and spatial correlations of commercial gentrification in Chengdu, a large Chinese city. With the data of points of interest (POIs), the study categorizes new retail places for commercial gentrification and conducts spatial and statistical analyses. The following findings are revealed: First, the distribution of new retail places changed from a monocentric to a polycentric structure in the main urban areas of Chengdu from 2010 to 2020, wherein high-density areas were partially overlapped with traditional commercial centers. Second, commercial gentrification in Chengdu was presented by the fastest growth of the entertainment services in the 2010s. Third, commercial gentrification in Chengdu shifted from a centripetal to a centrifugal development pattern from 2010 to 2020. The geographies of development were variegated, connected with multiple location attributes and impacted by local governments’ urban development strategies. Fourth, commercial gentrification was positively correlated with the growth of knowledge-intensive industries but negatively related to the change in both traditionally secondary and tertiary sectors in the past decade. Finally, changes in housing prices showed no connection with commercial gentrification during the studied period. The study suggests that commercial gentrification should be treated as a phenomenon of industrial gentrification, independent of residential gentrification. The commercial spatial planning in the city should play close attention to the synergic and exclusive relations between new retail industries and the evolution of industrial spaces in the emerging post-industrial city economy.